Defining Mental Health in Later Life. - Qualls, Sara Honn (Generations)
Part of a special issue on mental health and mental illness in later life. The writer considers the factors that constitute psychological well-being and stresses the importance of defining mental health. She describes traditional models for defining mental health and draws on lifespan psychology literature to present another set of frameworks for formulating a definition for mental health in later life. Furthermore, she offers a positive definition of mental health in later life and identifies research questions that provide focal points for future research on the validity of this definition and of frameworks on which it is based.